A Matter of Size and Stress: Understanding the First‐Order Transition in Materials for Solid‐State Refrigeration. (6th July 2017) - Gottschall, Tino; Benke, Dimitri; Fries, Maximilian; Taubel, Andreas; Radulov, Iliya A.; Skokov, Konstantin P.; Gutfleisch, Oliver
Abstract : Solid‐state magnetic refrigeration is a high‐potential, resource‐efficient cooling technology. However, many challenges involving materials science and engineering need to be overcome to achieve an industry‐ready technology. Caloric materials with a first‐order transition—associated with a large volume expansion or contraction—appear to be the most promising because of their large adiabatic temperature and isothermal entropy changes. In this study, using experiment and simulation, it is demonstrated with the most promising magnetocaloric candidate materials, La–Fe–Si, Mn–Fe–P–Si, and Ni–Mn–In–Co, that the characteristics of the first‐order transition are fundamentally determined by the evolution of mechanical stresses. This phenomenon is referred to as the stress‐coupling mechanism. Furthermore, its applicability goes beyond magnetocaloric materials, since it describes the first‐order transitions in multicaloric materials as well. Abstract : Solid‐state magnetic refrigeration is a high‐potential cooling technology. Materials with a first‐order transition are most promising because of their large adiabatic temperature and isothermal entropy changes. In this study, it is demonstrated with the magnetocaloric materials La–Fe–Si, Mn–Fe–P–Si, and Ni–Mn–In–Co, using experiment and simulation, that the characteristics of the first‐order transition are fundamentally determined by the evolution of mechanical stresses.